Dopamine‐conjugated extracellular vesicles induce autophagy in Parkinson's disease - Jae Hoon Sul; Sol Shin; Hark Kyun Kim; Jihoon Han; Junsik Kim; Soyoung Son; Jungmi Lee; Seung Hyun Baek; Yoonsuk Cho; Jeongmi Lee; Jinsu Park; Donghoon Ahn; et al. (Journal of Extracellular Vesicles)
Abstract The application of extracellular vesicles (EVs) as vehicles for anti‐Parkinson's agents represents a significant advance, yet their clinical translation is hampered by challenges in efficient brain delivery and complex blood‐brain barrier (BBB) targeting strategies. In this study, we engineered dopamine onto the surface of adipose‐derived stem cell EVs (Dopa‐EVs) utilizing a facile, two‐step cross‐linking approach. This engineering enhanced neuronal uptake of the EVs in primary neurons and neuroblastoma cells, a process shown to be competitively inhibited by dopamine pretreatment and dopamine receptor antibodies. Notably, Dopa‐EVs demonstrated increased brain accumulation in mouse Parkinson's disease (PD) models. Therapeutically, Dopa‐EVs administration led to the rescue of dopaminergic neuronal loss and amelioration of behavioural deficits in both 6‐hydroxydopamine (6‐OHDA) and α‐Syn PFF‐induced PD models. Furthermore, we observed that Dopa‐EVs stimulated autophagy evidenced by the upregulation of Beclin‐1 and LC3‐II. These findings collectively indicate that surface modification of EVs with dopamine presents a potent strategy for targeting dopaminergic neurons in the brain. The remarkable therapeutic potential of Dopa‐EVs, demonstrated in PD models, positions them as a highly promising candidate for PD treatment, offering a significant advance over current therapeutic modalities.